2022
DOI: 10.3389/fpsyg.2022.846238
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in the Psychosocial Functioning of Parents During the COVID-19 Pandemic

Abstract: The COVID-19 pandemic significantly affected family life, increasing parental stress around health, job losses, reduced salaries, and maintaining domestic life in lockdown and social isolation. The transition to home-schooling and remote work with school and workplace closures caused additional stressors as families began living, working, and educating in one place. This research aims to understand the relationship between the pandemic and parental stress, focusing on family well-being and established characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 31 publications
2
4
0
Order By: Relevance
“…Our result may be attributed to greater mental work taken by mothers during the pandemic than before the pandemic. A previous study showed that mothers who lacked support and had difficulty managing homeschool were generally more stressed than fathers (O'Sullivan et al, 2022). Hjálmsdóttir and Bjarnadóttir (2021) reported that mothers experienced intense emotional labor on the one hand while trying to keep everyone in their home calm and safe on the other hand.…”
Section: Discussionmentioning
confidence: 98%
“…Our result may be attributed to greater mental work taken by mothers during the pandemic than before the pandemic. A previous study showed that mothers who lacked support and had difficulty managing homeschool were generally more stressed than fathers (O'Sullivan et al, 2022). Hjálmsdóttir and Bjarnadóttir (2021) reported that mothers experienced intense emotional labor on the one hand while trying to keep everyone in their home calm and safe on the other hand.…”
Section: Discussionmentioning
confidence: 98%
“…Although from a biological perspective men were at greater risk and had more complications during the COVID-19 pandemic ( 50 , 51 ), certain gender impact has also been observed. As is well-known in the literature and among the scientific community, women present worse Self-Rated Health than men, so it is a constant today ( 52 , 53 ). Globally, women suffered more job losses than men.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, home confinement had a direct impact on household care work, mainly performed by women. Many women during this pandemic have had to make real efforts to reconcile work, teleworking and family life, and this has had a direct impact on their health and well-being ( 51 , 52 , 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…Guilt is a major driver of mothers' considerations to reduce employment 96 . Research in Ireland found that mothers were three times more likely to leave their jobs during the pandemic because they felt guilt around being a 'good mother' 97 . Organisational culture plays a critical role with mothers experiencing more guilt than fathers in workplaces that emphasize traditional gender norms 98 .…”
Section: Career Penalties For Caregivingmentioning
confidence: 99%